Carbonised Agro-Waste Adsorbents for Automotive Lubricating Oil Removal - Nivethah, Sokalinggam; Hasnida, Harun; Nurdalila, Saji; Nor Hazren, Abdul Hamid; Nor Maizzaty, Abdullah; Inawati, Othman; Noor Hasyimah, Rosman (Penerbit UTHM, 2025)
The increasing generation of waste lubricating oil, driven by expanding industrial and automotive activity, poses a significant threat to aquatic ecosystems due to its persistence, hydrophobicity, and complex chemical composition. This study evaluates two abundant agro-waste residues: rice husk (RH) and sugarcane bagasse (SB) as potential adsorbents for lubricating oil removal. Both biomasses were pre-treated with 1M NaOH to enhance surface porosity and hydrophobicity, followed by carbonisation at 550 °C. Three adsorbent formulations were prepared based on RH:SB weight ratios of 24:6, 15:15, and 6:24 g. Batch experiments were conducted at oil concentrations of 25, 30, and 35 v/v% and contact times of 10, 20, and 30 min using a fixed 30g adsorbent dosage of RH and SB. The response behaviour was further examined using ANOVA and contour-plot analysis under Response Surface Methodology to interpret factor interactions. Optimum values for RH-SB adsorbent are 15:15 g of adsorbent dosage, 25 v/v% of oil concentration and 30 min of contact time. These resulted in 100% removal efficiency under controlled batch conditions. FTIR analysis confirmed the presence of lignocellulosic structures supporting oil–adsorbent interactions. Overall, the findings demonstrate that carbonised RH and SB are viable, low-cost, and environmentally sustainable adsorbents and are strongly recommended for removing used lubricating oil.